The influence of media on hijab wearing in Malaysia: a study among Malays = Pengaruh media terhadap pemakaian hijab di Malaysia: satu kajian di kalangan orang Melayu - A. Manaf, Aini Maznina; Wok, Saodah (International Islamic University Malaysia (IIUM), 2019)
Hijab wearing among Muslim women is currently seen as a common phenomenon in Malay-sia. Is the religious awareness among them on the rise? Or is it just fashion or a trend? Many studies (Williams and Vashi, 2007; Furseth, 2011) have been conducted to understand factors that influence hijab wearing among Muslim women. Nonetheless, little information is available on the roles that the media play in influencing women’s decision to wearing the hijab. This study is conducted to find out the perception of Muslim women on the extent to which media and people surrounding them influence their hijab (head cover) wearing. Specifically, the objectives of this study are (1) to find out the patterns of hijab wearing, (2) to find out sources of media influence on hijab wearing among Malay women, (3) to determine sources of social/interpersonal influence on hijab wearing among Malay women, (4) to compare between the media influence and the social/interpersonal influence on hijab wearing among Malaysian women, and (5) to analyze the extent of media and social/interpersonal influence on impact change from hijab wearing. Using data from a survey conducted on 362 female students from an Islamic Higher Education Institution in Malaysia, the findings reveal that Facebook, blog and magazine are the top three highest media influencing impact change from hijab wearing. Parents, friends/colleagues and siblings have more influence on hijab wearing than the other sources. Social/interpersonal influence has a bigger impact than the media in influencing hijab wearing. In addition, both the media influence and the social/interpersonal influence are positively related to one another. The Malay women admit that hijab wearing has much/very much changed them towards being good Muslims.